Calcitonin gene relating peptide inhibitors in combination for migraine treatment: A mini-review - Shah, Tulsi; Bedrin, Kate; Tinsley, Amanda (Frontiers in Pain Research, 2023)
The discovery of calcitonin gene-related peptide (CGRP) and its role in migraine pathophysiology has led to advances in the treatment of migraine. Since 2018, the Food and Drug Administration (FDA) has approved four monoclonal antibody (mab) therapies targeting either the CGRP ligand or receptor and 3 oral small molecule CGRP receptor antagonists. These targeted therapies have been shown to be safe and effective for either preventive or acute treatment of migraine in adults. Given their efficacy and tolerability profile, CGRP inhibitors have revolutionized the approach to migraine treatment. Theoretically, combining therapies within this therapeutic class could lead to more CGRP blockade and, subsequently, improved patient outcomes. There are providers currently combining CGRP therapies in clinical practice. However, limited data are available regarding the efficacy and safety of this practice. This mini-review provides a summary of available data and poses important considerations when combining CGRP therapies for migraine treatment.